KAJIAN EKSPERIMENTAL FAKTOR REDAMAN BETON POLIMER DENGAN MODAL TESTING - Mohd Isneini (Jurnal Matematika Sains dan Teknologi, 2003)
Polimer concrete has different behaviour and different mechanic characteristic than others because it depends on material polimer that are used, so that it caused to be researched and be studied its behaviour and mechanic caracteristic.This polimer concrete was made of prepacked system, consisted of unsaturated polyester (UP) added with styrene monomer (SM) as binder matrix, cobalt napthenate solution (CoNp) as a promotor and methyl ethyl ketone peroxide (MEKPO) as an initiator, and coarse aggregate as inclusion. In this composition, variation of polymer concrete based on percentage of polimer and fly ash as a filler, and any other materials were keeped in constant.The object of this research are to find out values of damping (loss factor), dynamic parameter, so that series of laboratory tests were carried out. Test results showed, values of damping (loss factor) 1,669 – 3,017%. Results also showed that much and much more content of polymer caused loss factor (h ), damping coeffisien (c) and damping ratio (x ) decrease, however it showed that fly ash affected to increase value of dynamic parameter.